Pedagogia da Autonomia: Os Limitadores da Docência no Exercício da Autonomia na Instituição Escolar - Farinelli, Rosana Gonçalves Ferreiro (2010)
The main objective of this study is to identify whether there are elements present in the daily activities of the teacher who interfere with his ministry and quantify its influence, using the theoretical book "The Pedagogy of Autonomy" by Paulo Freire and the conceptual foundations of pedagogy Freirien. We gathered the routine of the institutions to establish the existence and extent of what we call here limiting the autonomy of teaching responsibility by reducing the capacity of teachers in working with students. Thus, events which is outside the teacher's action, often far from the same school environment, an environment in which the institution is situated, have reduced their participation in this autonomy. Other limiters have their genesis inside the educational environment, difficulting and sometimes preventing this action. Are limiting it by its intrinsic link with the institution, in terms of context, this paper classify as institutional. Excess activities that the teacher's subject and the avalanche bureaucratic forcing him sometimes to take part in its activities into your personal life, appear here as limiting functional, being closely linked to aspects of the practice the teacher. Even the physical barriers that ensure the tranquility of the school environment, such as badges, gates, turnstiles and others, are treated here as a physical limitation, writing with the other categories around which the subject matter hereof develops. There are in fact, limiting the educational action? To what extent have their effects and to what extent are felt by education? These are questions whose analysis will be grounded by responses given by teachers of early childhood education, elementary school I and II beyond high school, a questionnaire, which compiled and statistically treated will culminate in the hypothesis at the conclusion of this essay: "The educational activity suffers from the effects caused by limiting the action teacher . To this end we will establish the bases in the reference section first, cutting the work of the eminent educator elements that serve to its theoretical basis. Starting from the most generic to the specific nature, which have connotations with this issue, we in the second chapter to survey the various activities of their own educational practice, which the teacher has no way to escape, calling them didactically, in preparation a later time for data collection. In the third chapter is presented in the questionnaire and its results, the statistical methodology employed was qualitative, but with ratings that allow measuring the degree of interference in each category present in the final result. So I decided, according to the initial hypothesis, the existence of the limiting factors inherent in the educational practice and its importance as the inhibitors of the teaching activities within the universe studied(AU).